Evaluasi Tingkat Maturitas Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja COBIT 4.1 Domain Plan And Organise (Studi Kasus Pada Divisi TI PT.PAL Indonesia) - Dilla Kusumaningrum; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PAL Indonesia is a national maritime industry. This important role of PT. PAL Indonesia will bring Indonesia's maritime industry to fulfill the maritime market globally. There is Divisi Teknologi Informasi that supports the fulfillment of information technology (IT) requirements at PT. PAL Indonesia. To apply the principles of Good Corporate Governance (GCG) in the management of Information Technology (IT), it is necessary to develop IT governance that is an integral part of Enterprise Governance in order to guarantee the utilization of IT implementation. The Information Technology Division has several lacks in information technology governance such as incompatibility of tasks and responsibilities for each staff member or employee in the IT Division, lack of documentation of several IT governance processes, lack of integration of existing IT governance processes in the company, the handling of infrastructure is not optimal, and there is no regular evaluation of IT governance in the IT Division. Therefore, the purpose of this research is to find out the level of maturity of information technology governance in PT. PAL Indonesia using the COBIT 4.1 framework that focuses on the Plan And Organize (PO) domain. From the results of the research it can be seen the average value of the maturity level of each process in the PO domain. The maturity level of the PO domain is level 3, namely Defined Process. In order to increase the level of maturity, a recommendation can be applied to the Divisi TI of PT. PAL Indonesia so that it is able to reach the expected target.